2020
DOI: 10.1093/ecco-jcc/jjaa229
|View full text |Cite
|
Sign up to set email alerts
|

Increased Mucosal Thrombin is Associated with Crohn’s Disease and Causes Inflammatory Damage through Protease-activated Receptors Activation

Abstract: Background and Aims Thrombin levels in the colon of Crohn’s disease patients have recently been found to be elevated 100-fold compared to healthy controls. Our aim was to determine whether and how dysregulated thrombin activity could contribute to local tissue malfunctions associated with Crohn’s disease. Methods Thrombin activity was studied in tissues from Crohn’s disease patients and healthy controls. Intracolonic administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 40 publications
3
25
0
Order By: Relevance
“…An increased thrombin activity was measured in colonic samples from patients with Crohn’s disease. This increased activity and an increased thrombin expression were also observed in colonic tissue from TNBS-induced acute colitis rats [ 11 ]. A second trypsin-like protease reported to be involved in both IBD and IBS is tryptase [ 2 , 3 , 4 , 14 ].…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…An increased thrombin activity was measured in colonic samples from patients with Crohn’s disease. This increased activity and an increased thrombin expression were also observed in colonic tissue from TNBS-induced acute colitis rats [ 11 ]. A second trypsin-like protease reported to be involved in both IBD and IBS is tryptase [ 2 , 3 , 4 , 14 ].…”
Section: Introductionmentioning
confidence: 78%
“…There is ample evidence in literature for the involvement of proteases in IBS and IBD [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Most studies rely on the use of synthetic substrates for trypsin-like and elastase-like enzymes that are often not capable of making further refinements towards the specific proteases involved [ 4 , 8 , 9 , 10 , 11 , 12 , 13 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such deregulated proteolytic activity was shown to participate in the inflammatory response and to cause structural and functional alterations in the gut epithelium through (i) the activation of protease-activated receptor (PAR), (ii) the cleavage of junctional protein and (iii) the processing of cytokines and chemokines. A recent study demonstrated that the pro-inflammatory effects of colonic thrombin, whose activity showed a 100-fold increase in the biopsies of IBD patients [ 60 ], are mediated through the activation of PAR1 and PAR4 [ 61 ]. Only PAR1 inhibition prevents 2,4,6-Trinitrobenzenesulfonic acid (TNBS)-induced colitis in rats.…”
Section: Proteases As Key Targets In Intestinal Inflammationmentioning
confidence: 99%